2-Hydroxyethyl Cellulose as Natural Binder in Electrodes for Solid-state Proton Battery: Construction and Preliminary Results - M. A. Ramlli; Yu K. X.Yu; Y. W. Siew; M. I. N. Isa (Akademi Sains Malaysia, 2024)
Affordable and greener materials were extensively studied in electrode fabrication for Liion based batteries but less interest was shown to proton battery. Hence, in this work, a methodology on preparing a natural based binder for proton battery was reported. 2- Hydroxyethyl Cellulose (2HEC) was chosen to replace PVDF commercial binder in electrode for ZnSO4jMnO2 proton battery configuration. SEM image shows good surface formation for both anode and cathode with good porous structure. OCV result shows that the cell improved the stable voltage of reference cell of 0.7 V to 0.9 V after 24 hours. The first discharge of the cell took 6 hours and 49 minutes at 0.005mA and shows good potential for rechargebility test.